UJI Brine Shrimp Lethality Test (BSLT) UMBI BAWANG TIWAI (Eleutherine bulbosa (Mill.) Urb) DAN UJI TOKSISITAS AKUT FRAKSI AKTIF - Lestari, Dwi; Kartika, Rudi; Marliana, Eva (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2019)
Eleutherine bulbosa (Mill.) Urb come from the Iridaceae family, this species contains secondary metabolites in the form of flavonoids and quinones. This research method includes Brine Shrimp Lethality Test (BSLT) toxicity using Artemia salina Leach larvae to determine the LC50 value. This study used experimental methods pharmacologically using a completely randomized design in the same direction pattern in the selection of test animals, 25 animals used were white mice divided into 5 groups with 5 mice per group, with 4 hours observed to find out toxic symptoms and continued observation every 24 hours to see death. Testing of BSLT results showed that ethanol extract had LC50 toxicity = 66.68 ppm (very toxic category), n-hexane fraction had LC50 toxicity = 47.64 ppm (very toxic category), chloroform fraction had LC50 toxicity = 295.1 ppm ( toxic category), and the water fraction has a toxicity of LC50 = 194.54 ppm (very toxic category). The chloroform fraction is an active fraction. Acute toxicity test LD50 value according to the calculation method of Miller Tainter Probit (187,499 mg/KgBB), the method of calculation of Thompson Weil (182,810 mg/KgBB), how to calculate Indonesian Pharmacopoeia (187,068 mg/KgBB). Based on the three calculations, the LD50 value is in the medium category (50-500 mg/kgBB).